Alanine synthesized by alanine dehydrogenase enables ammonium-tolerant nitrogen fixation in Paenibacillus sabinae T27 - Li, Qin; Zhang, Haowei; Song, Yi; Wang, Minyang; Hua, Chongchong; Li, Yashi; Chen, Sanfeng; Dixon, Ray; Li, Jilun (Nevada RNformation, 2022)
Most diazotrophs fix nitrogen only under nitrogen-limiting conditions, for example, in the presence of relatively low concentrations of NH₄⁺ (0 to 2 mM). However, Paenibacillus sabinae T27 exhibits an unusual pattern of nitrogen regulation of nitrogen fixation, since although nitrogenase activities are high under nitrogen-limiting conditions (0 to 3 mM NH₄⁺) and are repressed under conditions of nitrogen sufficiency (4 to 30 mM NH₄⁺), nitrogenase activity is reestablished when very high levels of NH₄⁺ (30 to 300 mM) are present in the medium. To further understand this pattern of nitrogen fixation regulation, we carried out transcriptome analyses of P. sabinae T27 in response to increasing ammonium concentrations. As anticipated, the nif genes were highly expressed, either in the absence of fixed nitrogen or in the presence of a high concentration of NH₄⁺ (100 mM), but were subject to negative feedback regulation at an intermediate concentration of NH₄⁺ (10 mM). Among the differentially expressed genes, ald1, encoding alanine dehydrogenase (ADH1), was highly expressed in the presence of a high level of NH₄⁺ (100 mM). Mutation and complementation experiments revealed that ald1 is required for nitrogen fixation at high ammonium concentrations. We demonstrate that alanine, synthesized by ADH1 from pyruvate and NH₄⁺, inhibits GS activity, leading to a low intracellular glutamine concentration that prevents feedback inhibition of GS and mimics nitrogen limitation, enabling activation of nif transcription by the nitrogen-responsive regulator GlnR in the presence of high levels of extracellular ammonium.